Linking Social Media with E-Government Services (Saudi Arabia case study) - Aldera, Saja (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
Governments around the world are adapting the e-government initiative to provide new ways of delivering their services. The e-government initiative aims to increase government performance efficiency; however, there are a number of limitations facing the success of the e-government initiative. One of the key limitations is the citizens lack of knowledge about the e-government services which, in turn, requires an in-depth understanding of the citizens needs in order to provide them with the right service, at the right time. One way to accomplish this is by using the life-event approach, which is considered to be a citizen-centric approach that matches the citizens life-events with the needed e-government services. Moreover, with the increasing population using or organising their lives on social media, some services are turning to organising and recording a persons life. One such example is the timeline on Facebook, in which the events in a persons life are being recorded, and considered to be a source for capturing citizens life-events and needs. This research aims to develop a mechanism to advertise e-government services to citizens by using social media based on the life-event approach. Accordingly, the Social Media - Norm-Based Life-Event (SM-NoBLE) system is implemented with a mechanism for extracting citizens life-events from citizen interactions with social media. Then, it matches life-events with relevant e-services using the Norm-Based Life-Event (NoBLE) framework and the concept of norms borrowed from organisational semiotics for the matching mechanism. This research creates a case study of Saudi Arabia to apply the SM-NoBLE system to evaluate accuracy and functionality.